Thermal degradation behaviors and evolved products analysis of polyester paint and waste enameled wires during pyrolysis. (15th April 2020) - Liu, Wei; Wang, Na; Han, Junwei; Xu, Jiaqi; Li, Zihan; Qin, Wenqing
Highlights: Pyrolysis behaviors of polyester paint and waste enameled wires were studied. Pyrolysis gas of waste enameled wires were mainly composed of C2 H6 and C4 H8 O. Pyrolysis oil contained long chain hydrocarbons, long chain alkenes, and alcohols. Pyrolysis residues of polyester paint and waste enameled wires were analyzed. Abstract: The thermal degradation behaviors and evolved products analysis of polyester paint and waste enameled wires during pyrolysis were studied. Thermogravimetric (TG) and differential thermogravimetric (DTG) analyses were performed to investigate the mass loss characteristics. The pyrolysis solid residues generated during the process under optimal condition were detailedly analyzed by Fourier-transform infrared spectroscopy (FTIR). Meanwhile, the pyrolysis gas and oil generated were analyzed by gas chromatography-mass spectrometry (GC–MS). Kinetic analysis adopted the Ozawa–Flynn–Wall (OFW) model to confirm the reaction series by the variation pattern of activation energy. The results indicated that the pyrolysis of polyester paint and waste polyester enameled wires can be divided into three stages. The average activation energy of polyester paint and waste polyester enameled wires pyrolysis was 323.34 kJ/mol and 215.95 kJ/mol, respectively. The optimized pyrolysis temperature for polyester paint and waste polyester enameled wires was 500 °C and 900 °C, respectively. The chemical compositions of the pyrolysis residues of polyester paint and waste polyester enameled wires were basically same, mainly containing the compounds with CH, CO, aromatic ring, methyl, and aromatics bonds. The pyrolysis gas of polyester paint was mainly composed of C2 H6, while that of waste polyester enameled wires mainly consisted of C2 H6 and C4 H8 O. The main components of the pyrolysis oil polyester paint and waste polyester enameled wires were basically same, mainly containing long chain hydrocarbons, long chain alkenes, alcohols, phenol, ketone, aldehyde, and aromatic.